Website Profil Sebagai Media Informasi Sekolah dengan Wordpress di SDN 03 Wirogunan Kartasura Sukoharjo - Budiadi, Hasman; Setiyowati; Wibisono, Himawan (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
Information technology has developed rapidly and has become a need or new paradigm in today's social order. Educational institutions, especially SDN 03 Wirogunan, realize the need for a media or forum for delivering information that is in line with current developments and can be accessed by the school community quickly, easily and efficiently. By reviewing the right media with fast, easy and efficient conditions, the most suitable media is the internet. So that when conveying information you don't use manual methods. This is felt to be less practical and efficient, for this reason it is very necessary to create a Profile of SDN 03 Wirogunan as a media that provides information on various things about the school that are covered in one media. At the method stage, use WordPress as website creation software, MySQL as a database, Xampp as localhost, PHP as a programming language, UML as a flow aid for website creation, and Photoshop as graphics software. All of the software above are tools for creating a website. The final result of this activity is the creation of a profile website for SDN 03 Wirogunan, Kartasura District, Sukoharjo Regency using WordPress. Which aims as a means of school information